The intergenerational elasticity of earnings: Exploring the mechanisms - Uta Bolt; Eric French; Jamie Hentall-MacCuish; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2021)
Using data covering a single cohort's first 55 years of life, we show that most of the intergenerational elasticity of earnings (IGE) is explained by differences in: years of schooling, cognitive skills, investments of parental time and school quality, and family circumstances during childhood. To decompose the fraction of the IGE explained by each of these channels, we implement a multi-level mediation analysis combined with a latent factor framework that accounts for measurement error. Multilevel mediation analysis allows us to assess not only the direct effect of each channel on the IGE, but also its indirect effects working through the other channels, thus providing an in-depth understanding of the link between parents' and children's earnings. Of these channels, we show that the main driver of the IGE is increased levels of parental investments received by children of high income parents early in their lives, which encourages greater cognitive development and lifetime earnings.
Keywords: I24; J24; C38; 330; Parental Investments; Cognitive Skills; Intergenerational Elasticity of Earnings